Seleção de áreas aptas a disposição de lodo de estações de tratamento de esgoto com fins agrícolas - LESSA, Alyne Alves (2010)
Overcrowding in urban centers has spawned many impacts on the environment, highlighting the waste generated by their activities. To properly allocate these wastes, technologies are developed such as those involved in sewage treatment. However, this form of treatment also generates waste, which must be treated and disposed of properly. The sludge is a byproduct of sewage treatment and has few alternatives available, among which, the agricultural disposition for purposes of soil conditioning or recovery of degraded areas. The soil, however, must have received the favorable characteristics of this type of material so as not to create conditions for growth of bacteria is not eliminated in the sludge treatment and prevent contamination of groundwater and surface water. Thus, this study aimed to classify areas as to the suitability of the application of sludge sewage treatment station of Goiania, a radius of 46 km from that station, using the geographic information system. To achieve this goal, we proceeded to the identification of areas considered unsuitable to receive the sludge by CONAMA Resolution 375/2006 of MMA. Then, the areas that had no restrictions were analyzed for ability to use the land for sludge application from the characteristics of the following environmental factors: hydromorphism, fertility, texture, depth, drainage and stoniness of the soil, topography and beyond susceptibility to soil erosion. Studies for the radii of 46 and 20 km by the restrictions set by the resolution showed that the total area of study 25.5 and 43%, respectively, are unsuitable for sludge application, attending many of the weaknesses of the environmental field as observed for the hydromorphism factor and soil drainage. Since environmental factors texture, stoniness and depth restrictions were preventing the release of silt in some areas, while the fertility of the soil proved ideal for this purpose. Considering all the environmental factors, the area shows unfitness to sludge application on the order of 14.5% of the land to the radius of 46 km and 8.3% for the radius of 20 km, which added to the regulatory restriction excludes 40% and 51%, respectively, for this type of use. The areas suitable for agricultural sludge disposal account for 51.3% of total area, with 8.7% of the land with strong environmental restrictions on the radius of 46 km, while for the 20 km radius of these values are 45 and 3 7%, respectively. The best areas for sludge application in both areas - 20 km and 46 - are located in the northern study area.